Asuhan Keperawatan Pasca Partum Tindakan Sectio Caesarea Atas Indikasi Hipertensi Dalam Kehamilan - Ira Sukyati; Novianti Dwi Perwitasari (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2020)
Pregnant women with gestational age of 20 weeks often experience hypertension. Some of the factors that influence the occurrence of gestational hypertension are age (> 35 years), pregnancy factors, obesity, and a history of hypertension. The mortality rate due to hypertension in pregnancy in Indonesia is increasing, namely by 27.1% in 2015 and 33% in 2018. The purpose of a case study is to find out more about nursing problems that arise so that they are able to make proper planning and prevent complications such as pre eclampsia, eclampsia, placental abruption and others. Whereas in the fetus: stunted fetal growth in the uterus, premature birth, neonatal asphyxia, and fetal death. The population in this study was a client named Ny. D is female, 42 years old with married marital status and obtaining information sources from clients and family. Based on the research data, it was found that the results of nursing problems were the risk of decreased cardiac output, acute pain associated with physical injury agents, risk of infection, activity intolerance, fatigue, and ineffective breastfeeding. Keywords: sectio caesarea, hypertension in pregnancy, nursing diagnosis.